SARS-CoV-2 infection of phagocytic immune cells and COVID-19 pathology: Antibody-dependent as well as independent cell entry - Matveeva, Olga; Nechipurenko, Yury; Lagutkin, Denis; Yegorov, Yegor E.; Kzhyshkowska, Julia (Frontiers in Immunology, 2022)
Our review summarizes the evidence that COVID-19 can be complicated by SARS-CoV-2 infection of immune cells. This evidence is widespread and accumulating at an increasing rate. Research teams from around the world, studying primary and established cell cultures, animal models, and analyzing autopsy material from COVID-19 deceased patients, are seeing the same thing, namely that some phagocytic cells are infected or capable of being infected with the virus. Human phagocytes most vulnerable to infection include monocytes, macrophages, dendritic cells, and B cells. Convincing evidence has accumulated to suggest that the virus can infect monocytes and macrophages, while data on infection of dendritic cells and B cells are still scarce. Viral infection of immune cells can occur directly through cell receptors, but it can also be mediated or enhanced by antibodies through the Fc gamma receptors of phagocytic cells. Antibody-dependent enhancement (ADE) most likely occurs during the primary encounter with the pathogen through the first COVID-19 infection rather than during the second encounter, which is characteristic of ADE caused by other viruses. Highly fucosylated antibodies of vaccinees seems to be incapable of causing ADE, whereas afucosylated antibodies of persons with acute primary infection or convalescents are capable. SARS-CoV-2 entry into phagocytic cells can lead to abortive infection followed by host cell pyroptosis, which can trigger a massive inflammatory cascade, or to productive infection with the formation of viable virions. There may also be a third scenario, namely that of latent infection, but we have no actual evidence that this occurs. At least two hypotheses, not mutually exclusive, have been formulated that link immune cell viral infection and COVID-19 pathogenesis. The first is the hypothesis of an uncontrolled inflammatory cascade that results from pyroptosis of virus-infected monocytes and macrophages. The second is the Trojan Horse hypothesis, which is that infected phagocytes, hiding the virus inside themselves, can spread the infection throughout the body, infecting cells of different tissues and organs. Future research should show how true these hypotheses are.